2015
DOI: 10.3389/fpls.2015.00338
|View full text |Cite
|
Sign up to set email alerts
|

Carbon allocation during defoliation: testing a defense-growth trade-off in balsam fir

Abstract: During repetitive defoliation events, carbon can become limiting for trees. To maintain growth and survival, the resources have to be shared more efficiently, which could result in a trade-off between the different physiological processes of a plant. The objective of this study was to assess the effect of defoliation in carbon allocation of balsam fir [Abies balsamea (L.) Mill.] to test the presence of a trade-off between allocation to growth, carbon storage, and defense. Three defoliation intensities [control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 65 publications
5
42
0
Order By: Relevance
“…Recent studies in conifers have also reported a lack of evidence for trade-offs between constitutive defense levels and growth. In balsam fir (Abies balsamea), a member of the Pinaceae along with spruce, Deslauriers et al (2015) assessed the effect of defoliation on carbon allocation and found no evidence of trade-off with growth. In the same way, no evidence for trade-offs was found between growth and defense in Pinus pinaster (Sampedro et al 2011) and Pinus radiata (Moreira et al 2013).…”
Section: Trait Correlations and Trade-offs Between Resistance Againstmentioning
confidence: 99%
“…Recent studies in conifers have also reported a lack of evidence for trade-offs between constitutive defense levels and growth. In balsam fir (Abies balsamea), a member of the Pinaceae along with spruce, Deslauriers et al (2015) assessed the effect of defoliation on carbon allocation and found no evidence of trade-off with growth. In the same way, no evidence for trade-offs was found between growth and defense in Pinus pinaster (Sampedro et al 2011) and Pinus radiata (Moreira et al 2013).…”
Section: Trait Correlations and Trade-offs Between Resistance Againstmentioning
confidence: 99%
“…In Canada, aspen forests are primarily damaged by defoliator insects, especially forest tent caterpillar and large aspen tortrix (Cooke & Lorenzetti, 2006;Hogg, Brandt, et al, 2002;Huang et al, 2008). Following repeated and heavy defoliation, trees may lose vigor and cannot acquire adequate amounts of carbohydrates to support radial growth (Deslauriers, Caron, & Rossi, 2015;Hudgeons et al, 2007;Kosola, Dickmann, Paul, & Parry, 2001). Where some trees die as a result of insect outbreaks or drought, reductions in competition levels could lead to increases in growth of surviving trees (Axelson, Alfaro, & Hawkes, 2009;Berg, Henry, Fastie, De Volder, & Matsuoka, 2006;Bretfeld, Doerner, & Franklin, 2015).…”
Section: Effects Of Insect Outbreaks On Forest Declinementioning
confidence: 99%
“…Outbreaks of the eastern spruce budworm (Choristoneura fumiferana Clemens) are currently one of the major natural disturbances in the boreal forest (Bergeron et al 1995;Rossi and Morin 2011;Simard et al 2012). These events cause marked reductions in tree growth and increased stand mortality (Bouchard et al 2005;Zhang et al 2014). Drought is another important stress with rates of tree mortality in Canada's boreal forest increasing by 1.9% year −1 in the eastern part to 4.9% year −1 in the western portion between 1963 and 2008 (Peng et al 2011).…”
Section: Introductionmentioning
confidence: 99%